Sinteza in karakterizacija sulfoniranega polianilina - Mav Golež, Ida (Kovine zlitine tehnologije, 1999)
Sulfonated polyanilines (SPAN) were prepared by the copolymerization of aniline and 3-aminobenzensulfonic acid (metanilic acid) under different reacation conditions: the molar ratio between monomers, amount of oxidant ammonium peroxodisulfate, reaction temperature and time were waried. The composition of copolymers was determined by elemental analysis and atomic emission spectroscopy based on inductively coupled plasma (ICP-AES). We established the effect of the reaction conditions on the yields of syntheses. The average molar masses and polydispersities of the products were determined by size exclusion chromatography (SEC).
Keywords: polianilin; sulfonirani polianilin; sinteza; analiza; karakterizacija